Trade Creation and Trade Diversion in African RECs : Drawing Lessons for AfCFTA - Kassa, Woubet; Sawadogo, Pegdewende Nestor (World Bank, Washington, DC, 2021)
This study aims to draw key lessons for the African Continental Free Trade Area using evidence from within the region. Although drawing lessons from the rest of the world is essential, given the unique features of economies in the Africa region, the most relevant lessons can be drawn from the experiences of regional economic communities in the continent. The study draws on the eight regional economic communities that have been recognized by the African Union as pillars on which the continent will rely to implement the African Continental Free Trade Area. The study evaluates the trade creation and trade diversion impacts of each of the eight RECs and examines their performance with the goal of drawing lessons and identifying challenges for the success of the African Continental Free Trade Area. Despite significant heterogeneities, there is more trade creation than trade diversion and a generally positive impact on trade within the regional economic communities. Two regional economic communities in particular—the East African Community and the Southern African Development Community—outperform all the other regional economic communities in terms of boosting intra–regional economic community trade. This is mainly associated with the high level of investment in trade facilitation, the level of synergy between national and regional goals, the density of economic activity, and the advancement in the quantity and quality of regional infrastructure. There are also many challenges that policy makers should address to realize the objectives of the African Continental Free Trade Area and transform the continent. Learning from the regional economic communities is central. But, given the scope of the African Continental Free Trade Area, there is also a need to examine the transition from regional economic communities to the African Continental Free Trade Area, which is expected to be a sticky transition.